Breathing Processing to Help Maintain Health Includes Techniques and Benefits - Gianna Salonga; Vanessa Aunor (Newinera Publisher, 2021)
Breathing exercises are designed and performed to achieve more controlled and efficient ventilation. The dilation of blood vessels affects blood pressure, which is to reduce the resistance to blood flow, so that blood pressure tends to be normal. Holding your breath also helps to increase your concentration, and stabilizes your emotions. Thoughts and emotions feel more stable and it is easy to concentrate on holding your breath. In breath-holding meditation practice is very helpful in increasing concentration. By holding your breath when the lungs are filled with air or empty, the process of taking oxygen by the blood stops, resulting in a lack of oxygen in the blood. This condition stimulates the blood to form more Hb cells, so that when you inhale, the amount of oxygen absorbed by the blood increases, as well as when you exhale, the amount of CO2 that is removed is also greater. The holding of breath will also cause a decrease in the amount of oxygen in the body's tissues, which increases the acidity of the body's tissues. The process of moving air in and out of the lungs to facilitate gas exchange with the body's internal environment, primarily by introducing oxygen and removing carbon dioxide. Breathing exercises are designed and performed to achieve more controlled and efficient ventilation.